2005
DOI: 10.3801/iafss.fss.8-999
|View full text |Cite
|
Sign up to set email alerts
|

Flame Heat Transfer Between Parallel Panels

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Therefore, we set the convection coefficient to h = 15 W/(m 2 K) here, in line with the value reported in [3].…”
Section: Cone Calorimeter Set-upmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, we set the convection coefficient to h = 15 W/(m 2 K) here, in line with the value reported in [3].…”
Section: Cone Calorimeter Set-upmentioning
confidence: 67%
“…fuel sootiness [3,4] is avoided. To summarise, expressions as developed in [3] for a similar set-up as the one under study in the present paper, are not applied here, but the present paper is not intended to provide an alternative for such relationships.…”
Section: Introductionmentioning
confidence: 99%
“…[16], were fitted to flame heat transfer measurements obtained from a larger parallel panel apparatus for which radiative heat transfer was dominant. However, the separation distance, d for the current study is only half as large (0.153 m) resulting in proportionately less radiative heat transfer and an enhanced role for convective heat transfer.…”
Section: Fire Growth Time Constantmentioning
confidence: 99%
“…The model is based on a semi-empirical treatment for radiation dominated flame heat transfer to panels characterized by: (1) fuels in terms of their flame sootiness, (2) fire heat release rates, and (3) panel width to separation aspect ratios [16]. The properties of the various corrugated paperboards used in the study (critical heat flux, flame sootiness in addition to the heats of combustion and gasification) are all obtained from small-scale measurements of ignition, combustion and pyrolysis using the FPA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ingason performed free burning reduced scale (scale 1:3) and full scale tests with corrugated paper cardboard box arrays and measured the centreline temperatures and gas velocities between the racks [13]. An investigation of heat fluxes to the surface in a two parallel plate configuration and in the middle of four modelled storage racks was done by de Ris and Orloff [14]. Several different fuels were used in these studies and it was shown that the heat flux from flames is sensitive to the flame sootiness.…”
mentioning
confidence: 99%